Віртуальні виставки: нові можливості у соціально-комунікаційних інституціях - Білущак, Тетяна; Акиджи, Валерія (Видавництво Львівської політехніки, 2018)
The article considers the creation of virtual exhibitions as a tool for popularizing goods or services. In particular, the virtual library exhibition is being considered, it provides cumulation, storage and general availability of documents, information, knowledge. Also, the article analyzes programs that are used to create virtual exhibitions.
Keywords: віртуальні виставки; соціально-комунікаційні інституції; виставкова діяльність; оцифрування; популяризація документів